2012
DOI: 10.3109/0886022x.2011.649658
|View full text |Cite
|
Sign up to set email alerts
|

Time-Course Evaluation of Oxidative Stress-Related Biomarkers after Renal Transplantation

Abstract: Patients with chronic renal disease have a high prevalence of oxidative stress (OS), which is associated with the cardiovascular complications occurring in this population. The restoration of kidney function after kidney transplantation (KT) can lead to reduction in the metabolic abnormalities and elimination of the OS. Time-dependent changes in OS-related markers and specific kidney function and metabolic parameters were evaluated in patients (N = 39; 23 males; 16 females; mean age = 57 ± 10 years) before (da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 23 publications
1
16
1
Order By: Relevance
“…Our findings are congruent with other studies which reported decreased TAOC at 12 days [20], 6 months [21] and 12 months [22] after kidney transplantation. However, the mechanism which induced decreased TAOC is controversial.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are congruent with other studies which reported decreased TAOC at 12 days [20], 6 months [21] and 12 months [22] after kidney transplantation. However, the mechanism which induced decreased TAOC is controversial.…”
Section: Discussionsupporting
confidence: 93%
“…It was suggested that it might be caused by the reduction of uric acid which may lead to major variations of the internal redox state [20]. Meanwhile, it was also suggested that TAOC may not be related or insufficiently sensitive to oxidative stress after kidney transplantation [21, 22]. Immunosuppressant is considered to be an important factor for the change of TAOC, however, the effect of immunosuppressant is also controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Although, oxidative injury appears to decrease in the first week after Tx, it stays elevated in later post-transplantation period in comparison to healthy individuals (Vostálová et al, 2012) and may result from the end stage renal disease (ESRD)-associated oxidative stress, immune response to allograft, ischemia reperfusion http://dx.doi.org/10.1016/j.ejps.2015.01.013 0928-0987/Ó 2015 Elsevier B.V. All rights reserved. injury, opportunistic infections, and immunosuppressive therapy (Campise et al, 2003;Naesens et al, 2009).…”
Section: Introductionmentioning
confidence: 85%
“…Oxidative stress is supposed to be associated with the pathophysiology of cardiovascular complications of ESRD. Restoration of kidney function after kidney transplantation has been shown to mitigate oxidative stress (7).…”
Section: Introductionmentioning
confidence: 99%